Psychoanalysis Criticism on John Keats Poem: When I Have Fears That I May Cease to Be - Febri Aspitasari (University of Darussalam Gontor, 2022)
This study was considered library research. This study was focused on analyzing a poem entitled “When I Have Fears That I May Cease to Be” written by John Keats using psychoanalysis criticism theory that was proposed by Sigmund Freud in 1952. The limitation of this study was about the author’s life including psychological aspect, experience, and author’s feeling that affected the poetry. The qualitative method was used in order to present the result of the analysis. The result of the analysis showed the three aspects, such as psychological aspect, author’s experience, and also the feelings are link together and affected the beauty of the poem. John Keats not only entertaining the reader but also educated the reader, through the theme that Keats brings to this poem, invite the reader to always being grateful and always do the best to improve our life to be better.